CLINICAL AUDIT – RIGHT TIME TO TAKE A START - Anwar, Ambreen (Pakistan Armed Forces Medical Journal, 2011)
Clinical audit is the review of performance, the refining of clinical practice as a result and measurement of performance against agreed standards - a cyclical process of improving the quality of clinical care. One of first ever clinical audits was undertaken by Florence Nightingale during the Crimean War of 1853-18551. Upon arrival at the medical barracks hospital in Scutari in 1854, Florence was appalled by the unsanitary conditions and high mortality rates among injured or ill soldiers. Working in an era where there were neither antibiotics nor modern antiseptics she and her team of 38 nurses applied strict sanitary routines and standards of hygiene to the hospital and equipment. Florence’s gift with mathematics and statistics, helped meticulous records of the mortality rates among the hospital patients.